Classification of intellectual disability according to domains of adaptive functioning and between‐domains discrepancy in adults with epilepsy. - Ool, J. S.; Snoeijen‐Schouwenaars, F. M.; Tan, I. Y.; Schelhaas, H. J.; Aldenkamp, A. P.; Hendriksen, J. G. M. (Journal of Intellectual Disability Research, 2019)
Background: In the Diagnostic and Statistical Manual of Mental Disorders–Fifth edition (DSM‐5), the diagnostic criteria of intellectual disability (ID) include three domains of adaptive deficits: the conceptual, social and practical. Substantial intra‐individual differences between domains can be considered an ID domain discrepancy. Method: We explored the associations between ID domains, discrepancies and epilepsy in 189 adults (mean age = 47.9; SD = 15.6). Each DSM‐5 ID domain was assessed separately, using subscales of the Vineland II for the social and practical domains, and psychological instruments, including intelligence tests, for the conceptual domain. A set of standardised criteria is proposed to identify an ID domain discrepancy. Results: An ID domain discrepancy seemed to be present in about one‐third of subjects and was particularly present in subjects with moderate ID (53.4%). Impairment in the social domain was most often the reason for the discrepancy. The presence of a discrepancy was significantly related to a focal (localised) epilepsy type (OR = 2.3, P = .028) and a mixed seizure type (OR = 1.4, P = .009). Epilepsy characteristics that are indicative of a more severe and refractory epilepsy, including various seizure types, a high seizure frequency, a combined epilepsy type (both focal and generalised epilepsy) and an early age at onset, were significantly related to more severe impairments in conceptual, social and practical adaptive behaviour (all P values <.01). Conclusions: With a substantial proportion of the subjects who had both ID and epilepsy with an ID discrepancy, professionals should be aware of this and take all domains of ID into account when studying or working with this vulnerable population.